The Moral and Value Message of Islam in Film "Udah Putusin Aja" (Semiotics Analysis of Charles Sanders Peirce) - Hesti Nurhidayati; Lilik Hamidah (Proceedings of International Conference on Da'wa and Communication, 2019)
The field of the film is currently attracting the attention of all citizens. Although the film has many other forms of mass media, it has special effects on those who view it. The "final decision" film is a recent release, with many moral messages given in the background of the teen's story. This study aims to determine what and how the representations, objects, interpretants, and moral messages are contained in “Udah Putusin Aja” film. To describe this problem, the researcher used the Charles Sanders Peirce model of the semiotic analysis method and the framework of cultural norm theory. The results of this study are representations of moral messages depicted in the dialogue of the players. Furthermore, the object is something that is represented. In relation, the objects here can be seen in the speech style, body gestures, and dialogue with moral messages that appear assigned. The interpretant is someone's interpretation of signs. The conclusion of the moral message in “ Udah Putusin Aja” film: always say greetings, wear a headscarf, do not come into contact with non-Muslim women, maintain honor for Muslim women, help each other, remind of death, prohibition of dating, don’t prejudice Allah SWT's plan, and apologize and forgive each other.